Bamboo zero: modelling bamboo as a carbon sink for net-zero carbon construction - Amir, Atikah Fukaihah; Foong, Swee Yeok; Ilias, Nur Hanim; Mansor, Azran; Meor Razali, Meor Abdullah Zaidi (2025)
The construction industry is one of the largest contributors to global greenhouse gas emissions, primarily due to its dependence on carbon-intensive materials such as concrete and steel. In Malaysia, addressing these emissions is critical to meeting the national target of achieving net-zero carbon emissions by 2050. Despite policy frameworks like the Low Carbon Cities Framework (LCCF) and the Low Carbon Cities 2030 Challenge (LCC2030C), practical, scalable solutions remain limited, particularly those that integrate both environmental and socioeconomic sustainability. Bamboo Zero responds to this urgent need by modelling bamboo as a carbon sink within the construction sector. Known for its rapid growth and high carbon sequestration capacity, bamboo presents a locally available, renewable alternative. Scientific modelling from results shows that every 1m³ of bamboo can sequester up to 0.54 tons of Carbon, reducing the embodied carbon of building materials significantly. By replacing or complementing conventional materials, Bamboo Zero contributes directly to carbon reduction in the built environment. Beyond environmental benefits, the innovation also promotes eco-entrepreneurship by empowering local bamboo farmers, builders, and green businesses, supporting the circular economy and creating green jobs. This dual-impact model aligns with Malaysia’s sustainable development goals, integrating low-carbon design, urban resilience, and community empowerment. Ultimately, Bamboo Zero is more than a material solution. It is a transformative framework that demonstrates how nature-based materials can be leveraged to create a net-zero carbon construction future while uplifting local economies and reinforcing climate resilience strategies.